The MedXFit-study – CrossFit as a workplace health intervention: a one-year, prospective, controlled, longitudinal, intervention study - Brandt, Tom; Heinz, Elisabeth; Klaaßen, Yannik; Limbara, Selina; Mörsdorf, Marian; Schinköthe, Timo; Schmidt, Annette (Frontiers in Public Health, 2024)
Purpose Workplace health interventions aim to motivate employees towards healthy behaviors to improve fitness and health in the long-term. We investigated whether CrossFit® is an effective training concept to achieve these goals in inactive employees with sedentary occupations. Methods The study followed a prospective, controlled intervention design. Employees were invited to participate in intervention group (IG) or control group (CG) on their own preferences. Inclusion criteria were a predominantly sedentary occupation and execution of less than two muscle and/or mobility enhancing training sessions per week at the time of enrolling. The IG did at least two times a week a CrossFit training of 1h. Mobility, strength, well-being, and back-issues were measured at the beginning, after 6, and 12 months. Participants in the CG were free to choose any other activities offered at the same time (e.g., circuit training, meditation, full body stability training). Adherence respectively behavioral change and maintenance qualities were evaluated based on the COM-B system and presence of behavior maintenance motives. Results 89 employees were enrolled into the trial, from where 21 dropped out due to external factors (24 %). From the remaining participants, 10 out of 39 (26 %) in the IG and 1 out of 29 (4 %) in the CG stopped for intrinsic reasons, leading to a non-adherence to the intervention of 22 percentage points. Motivation for behavioral change and maintenance in the IG was primarily driven by enhanced physical and psychological capability. Development of physical capability was evident by significant improvements (p<.001) in the IG compared to the CG for mobility (d=3.3), maximal isometric strength (min. d=1.7, max. d=2.5), as well as reduction in pain intensity (p=.003, r=.4) and frequency (p=.009, r=.35) after 12 months. Significant improvements between the 6-month and the 12-month measurement in mobility and 6 out of 8 strength measures within the IG indicated the effectiveness of CF beyond the beginner phase. Conclusion CrossFit is a motivating training concept that led to long-term health and fitness improvements in inactive employees doing sedentary work and should be given greater consideration in workplace health promotion.